2020
DOI: 10.1186/s40644-020-00322-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic value of tumor volumetric parameters in melanoma patients undergoing 18F-FDG-PET/CT: a comparison with serologic markers of tumor burden and inflammation

Abstract: Background To investigate the association of tumor volumetric parameters in melanoma patients undergoing 18F-FDG-PET/CT with serologic tumor markers and inflammatory markers and the role as imaging predictors for overall survival. Methods A patient cohort with advanced melanoma undergoing 18F-FDG-PET/CT for planning metastasectomy between 04/2013 and 01/2015 was retrospectively included. The volumetric PET parameters whole-body MTV and whole-body TLG as well as the standard uptake value (SUV) peak were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…More recently, a study by Reinert et al demonstrated the prognostic value of metabolic parameters in patients with melanoma regarding progression-free and overall survival [22]. This study demonstrated a positive correlation between MTV and TLG with overall and progression-free survival [22]. These findings were almost similar to our findings; however, this was done on a European population that presumably has better access to healthcare.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…More recently, a study by Reinert et al demonstrated the prognostic value of metabolic parameters in patients with melanoma regarding progression-free and overall survival [22]. This study demonstrated a positive correlation between MTV and TLG with overall and progression-free survival [22]. These findings were almost similar to our findings; however, this was done on a European population that presumably has better access to healthcare.…”
Section: Discussionsupporting
confidence: 89%
“…Due to mostly delayed presentation in our patient population, our study evaluated patients that demonstrated disease in the primary tumor at restaging with distant metastases. Our patients had significantly higher tumor volumes compared to what has been described by other authors [11,22].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The role of volumetric parameters in FDG-PET/CT as a predictive biomarker has been demonstrated in different types of cancers [5,[13][14][15][16][17]. The total metabolic tumor volume is a valuable parameter as it reflects the extent and activity of the tumor [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…High baseline (metabolically active) tumour burden is associated with worse treatment outcome and poor survival in patients with metastatic melanoma [11,[13][14][15][16]. Total body positron emission tomography (PET) using the glucose analogue 2-deoxy-2-[fluorine-18] fluoro-D-glucose ( 18 F-FDG) is part of standard baseline work-up in metastatic melanoma [13].…”
Section: Introductionmentioning
confidence: 99%